Sweet reckoning eaudiobook - Higgins, Wendy (Sweet Trilogy, 2014)
Fans of Cassandra Clare's Mortal Instruments series will be drawn to Wendy Higgins's sexy, thrilling Sweet Evil series. In Sweet Reckoning, the time has come for Anna, daughter of a guardian angel and a fallen one, to accept her fate as the chosen one. She is destined to rid the earth of demons once and for all. But as Anna and her Nephilim allies prepare for the evil brewing, the powerful Dukes use Anna's love for bad boy Kaidan Rowe against her, and her strength is put to the ultimate test. How far will the two of them go to keep each other alive? Will love conquer all in the final battle between good and evil?